Anemia in Human Immunodeficiency Virus Infection: Exploring the Interplay Between Antiretroviral Therapy, Opportunistic Infections, Iron Status, and Anemia - Murtiani, Farida; Tanjungsari, Dian Wahyu; Shidiq, Achmad; Herlina, Herlina; Dinar Widiantari, Aninda; Nurhayati, Nurhayati; Wirasmi, Sundari; Despitasari, Mieska; Yulianto, Aris; Hendarwan, Harimat (Public Health of Indonesia, 2024)
Background:Anemia is a prevalent hematological complication among individuals with Human Immunodeficiency Virus (HIV), contributing significantly to increased morbidity and mortality. This study investigates the intricate relationships between antiretroviral therapy (ART), opportunistic infections (OIs), iron metabolism, and anemia in HIV-positive patients in Indonesia. Objective:To elucidate the multifactorial associations among ART regimens, opportunistic infections, iron biochemical parameters, and anemia development in individuals living with HIV. Method:A cross-sectional epidemiological study was conducted at Sulianti Saroso Infectious Disease Hospital, Indonesia, from July to November 2023. The study involved 300 adult HIV-positive patients undergoing ART, with exclusion criteria encompassing pregnant or postpartum individuals, those with recent blood transfusions, and patients with chronic kidney diseases. Data collection included anemia status, ART regimen details, history of opportunistic infections, and iron metabolic profiles (serum iron, total iron-binding capacity [TIBC], and ferritin levels). These were obtained through systematic medical record reviews and laboratory diagnostics. Descriptive statistics, bivariate, and multivariate analyses were employed to explore predictive factors for anemia. Results:The study identified an anemia prevalence of 24.3%, with significantly higher rates among female patients (p = 0.004) and older age groups (p = 0.031). Multivariate regression analysis highlighted critical predictors of anemia: second-line ART (adjusted odds ratio [AOR]: 2.536, p = 0.028), serum iron concentrations (AOR: 0.984, p < 0.001), ferritin levels (AOR: 1.002, p = 0.023), and absolute lymphocyte count (AOR: 0.516, p = 0.003). Conclusion:The findings emphasize the necessity of longitudinal monitoring of hematologic and biochemical parameters to enhance anemia management in HIV-infected populations. The complex interplay between ART regimens, immune status, and iron metabolism underscores the importance of tailored, patient-centered clinical interventions.  Keywords:anemia; HIV; antiretroviral therapy; opportunistic infections; iron metabolism